Assessing genotype-phenotype associations in three dorsal colour morphs in the meadow spittlebug Philaenus spumarius (L.) (Hemiptera: Aphrophoridae) using genomic and transcriptomic resources. Issue 1 (December 2016) - Rodrigues, Ana; Silva, Sara; Pina-Martins, Francisco; Loureiro, João; Castro, Mariana; Gharbi, Karim; Johnson, Kevin; Dietrich, Christopher; Borges, Paulo; Quartau, José; Jiggins, Chris; Paulo, Octávio; et al.
Abstract Background Colour polymorphisms are common among animal species. When combined with genetic and ecological data, these polymorphisms can be excellent systems in which to understand adaptation and the molecular changes underlying phenotypic evolution. The meadow spittlebug, Philaenus spumarius (L.) (Hemiptera, Aphrophoridae), a widespread insect species in the Holarctic region, exhibits a striking dorsal colour/pattern balanced polymorphism. Although experimental crosses have revealed the Mendelian inheritance of this trait, its genetic basis remains unknown. In this study we aimed to identify candidate genomic regions associated with the colour balanced polymorphism in this species. Results By using restriction site-associated DNA (RAD) sequencing we were able to obtain a set of 1, 837 markers across 33 individuals to test for associations with three dorsal colour phenotypes (typicus, marginellus, andtrilineatus ). Single and multi-association analyses identified a total of 60 SNPs associated with dorsal colour morphs. The genome size ofP. spumarius was estimated by flow cytometry, revealing a 5.3 Gb genome, amongst the largest found in insects. A partial genome assembly, representing 24% of the total size, and an 81.4 Mb transcriptome, were also obtained. From the SNPs found to be associated with colour, 35% aligned to the genome and 10% to the transcriptome. Our data suggested that major loci, consisting of multi-genomic regions, may be involved in dorsal colour variation among the three dorsal colour morphs analysed. However, no homology was found between the associated loci and candidate genes known to be responsible for coloration pattern in other insect species. The associated markers showed stronger differentiation of thetrilineatus colour phenotype, which has been shown previously to be more differentiated in several life-history and physiological characteristics as well. It is possible that colour variation and these traits are linked in a complex genetic architecture. Conclusions The loci detected to have an association with colour and the genomic and transcriptomic resources developed here constitute a basis for further research on the genetic basis of colour pattern in the meadow spittlebugP. spumarius .